2020
DOI: 10.30565/medalanya.587027
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery (ERAS) and anesthesia

Abstract: ÖZERAS (Enhanced recovery after surgery) perioperatif yönetimi optimize etmeyi amaçlayan multimodal bir yaklaşımdır. ERAS, organ disfonksiyonunu ve cerrahi stres yanıtını azaltmak için preoperatif, intraoperatif ve postoperatif bakımdaki değişikliklerin bir bütünüdür. Bu kavram hastanın cerrahi stres yanıtını azaltmak, fizyolojik fonksiyonlarını düzeltmek ve iyileşmeyi kolaylaştırmak amacıyla çeşitli uzmanlık alanlarını içeren multidispliner ekipler tarafından yönetilir. Günümüzde değişik cerrahi uzmanlık alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…However, it was determined that the time to ambulation of patients with nausea and vomiting was delayed, and there was a significant difference in terms of nausea. Further, studies have reported that nausea and vomiting lead to reluctance to stand up in patients and thus, delay ambulation (30). Additionally, a reluctance to consume food may develop in patients with nausea.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was determined that the time to ambulation of patients with nausea and vomiting was delayed, and there was a significant difference in terms of nausea. Further, studies have reported that nausea and vomiting lead to reluctance to stand up in patients and thus, delay ambulation (30). Additionally, a reluctance to consume food may develop in patients with nausea.…”
Section: Discussionmentioning
confidence: 99%
“…2 Protokol ini bertujuan mengurangi stress respons akibat pembedahan, optimalisasi pemulihan, dan mengurangi lama rawat di rumah sakit. 3 Pasien yang mengalami komplikasi pascaoperasi mengalami peningkatan risiko morbiditas dan mortalitas jangka pendek dan jangka panjang.…”
Section: Pendahuluanunclassified
“…15 Selain itu, Teeuwen dkk, dalam penelitiannya mengenai perbandingan ERAS dan perawatan pascaoperasi konvensional pada pasien pembedahan kolorektal juga mendapati hasil yang serupa, kelompok ERAS dengan median lama rawat 6 (3-50) berbanding 9 (3-138) hari, dengan angka mortalitas yang lebih rendah. 3 Pada penelitian ini, terdapat beberapa keterbatasan. Pertama, terdapat beberapa luaran yang tidak diukur selama penelitian, seperti jumlah kebutuhan opioid yang digunakan pada kedua kelompok, waktu yang dibutuhkan untuk pelepasan kateter urine, serta komplikasi yang timbul selama perawatan yang dapat mempengaruhi lama rawat pasien.…”
Section: Pembahasanunclassified